Using TikTok in recovery from substance use disorder. (1st December 2021) - Russell, Alex M.; Bergman, Brandon G.; Colditz, Jason B.; Kelly, John F.; Milaham, Plangkat J.; Massey, Philip M.
Abstract: Background: There are many effective treatment options for substance use disorder (SUD), yet most individuals with SUD do not seek formal treatment services. Given the rising popularity of TikTok and need to foster innovative means through which to attract and engage individuals with SUD with treatment, we sought to characterize how TikTok users in SUD recovery are using this platform to bolster their recovery support and/or give hope to others who are struggling with substance use. Methods: Our sample consisted of 82 of the most liked TikTok videos related to attempts to cut down on or abstain from substances and/or strengthen SUD recovery. We employed an iterative process to codebook development resulting in codes for demographics, user-sentiment, video type, and mechanisms of recovery-related behavior change. Videos were independently double-coded and evaluated for inter-rater reliability. Results: Video in this sample were heavily viewed, accounting for over 2 million views per video and 325, 000 likes on average. Most common video themes were sharing a journey from active SUD to recovery (40.2%) and sharing/celebrating a recovery milestone (37.8%), followed by recurrence of substance use (12.2%). Commonly exemplified mechanisms of recovery-related behavior change included embracing a strong social identity as a person in recovery (81.7%), social support (45.1%), and participation in rewarding alternative activities (39.0%). Conclusion: TikTok SUD recovery-focused videos can potentially reach millions with portrayed themes similar to established therapeutic mobilizers and mechanisms. More research is needed to better understand whether digital recovery narratives can effectively normalize experiences of addiction and help-seeking behaviors. Highlights: Individuals are using TikTok as a part of their SUD recovery. Videos portrayed recovery journeys, milestones/successes, and struggles. Individuals depicted often demonstrated a strong social identity in recovery. Common references made to social support and alternative rewarding activities. Digital recovery narratives may serve to normalize help-seeking behaviors.